Leading green, acting green: How green commitment mediates and environmental self-efficacy moderates the eco-centric leadership-OCBE relationship in eco-friendly hotels - Hassan Abdou, Ahmed (Frontiers in Sustainability, 2025)
PurposeThis study aims to explore the mechanisms by which eco-centric leadership (Eco-L) influences Organizational Citizenship Behavior for the Environment (OCBE) among employees in Saudi eco-friendly hotels. It investigates the mediating role of green commitment (G-Com) and the moderating role of environmental self-efficacy (ESE) within this relationship.Design/Methodology/ApproachThe study employs a cross-sectional survey design using a structured questionnaire to collect data from employees working in five-star eco-certified hotels in Saudi Arabia. This design involved gathering data at a single point in time to capture employees' perceptions and attitudes. The proposed conceptual model was tested using PLS-SEM.FindingsThe results reveal that Eco-L has a positive and significant effect on OCBE. Furthermore, green commitment (G-Com) significantly mediates this relationship, indicating that employees' psychological attachment to green values enhances their voluntary environmental behaviors. In addition, ESE positively moderates the relationship between Eco-L and OCBE, suggesting that the impact of eco-centric leadership is stronger among employees with greater confidence in their environmental capabilities.Originality/ValueThis study makes a novel contribution by integrating Social Exchange Theory (SET) and Social Cognitive Theory (SCT) to explain the psychological and behavioral mechanisms linking leadership to pro-environmental behavior. While prior research has examined green commitment as a mediator and environmental self-efficacy as a moderator separately, this study is among the first to simultaneously explore these constructs within the combined SET and SCT framework. Furthermore, it applies this integrated approach specifically to the hospitality industry's eco-friendly hotel sector in Saudi Arabia—an underexplored context. The findings provide valuable insights into sustainable human resource management and leadership practices in this setting.